Assignment and modeling of the absorption spectrum of 13CH4 at 80 K in the region of the 2ν3 band (5853–6201 cm−1). (July 2016) - Starikova, E.; Nikitin, A.V.; Rey, M.; Tashkun, S.A.; Mondelain, D.; Kassi, S.; Campargue, A.; Tyuterev, Vl.G.
Abstract: The absorption spectrum of the 13 CH4 methane isotopologue has been recently recorded by Differential Absorption Spectroscopy (DAS) at 80 K in the 5853–6201 cm −1 spectral range. An empirical list of 3717 lines was constructed for this spectral range corresponding to the upper part of the Tetradecad dominated by the 2 ν 3 band near 5987 cm −1 . In this work, we present rovibrational analyses of these spectra obtained via two theoretical approaches. Assignments of strong and medium lines were achieved with variational calculations using ab initio potential energy (PES) and dipole moment surfaces. For further analysis a non-empirical effective Hamiltonian (EH) of the methane polyads constructed by high-order Contact Transformations (CT) from an ab initio PES was employed. Initially predicted values of EH parameters were empirically optimized using 2898 assigned line positions fitted with an rms deviation of 5×10 −3 cm −1 . More than 1860 measured line intensities were modeled using the effective dipole transition moments approach with the rms deviation of about 10%. These new data were used for the simultaneous fit of the 13 CH4 Hamiltonian parameters of the Ground state/Dyad/Pentad/Octad/Tetradecad system and the dipole moment parameters of the Ground state-Tetradecad system. Overall, 10 vibrational states and 28 vibration sublevels of the 13 CH4 Tetradecad are determined. The comparison of their energy values with corresponding theoretical calculations is discussed. Highlights: Experimental 13 CH4 spectra at 80 K were analyzed in 5853–6201 cm −1 region. 1744 rovibrational energy levels of the high edge of the Tetradecad were determined. 2900 line positions were theoretically modeled with RMS deviation of 0.005 cm −1 . 1900 experimental line intensities were fitted with RMS deviation of 10%. Assigned experimental and theoretical line lists at 80 K are provided.